A BRIEF ANALYSIS OF THE PROBLEMS OF SOIL SCIENCE AND MODERN EDUCATION (Scientific journal of the Fergana State University, 2025)
This article examines the problems of soil science and modern education, and highlights the importance of soil science in solving global environmental problems. It presents the current state of soil science, the main problems of modern educational practice, and ways to improve students' understanding of soil science. Through literature review and case studies, this article highlights the need to improve pedagogical approaches in teaching soil science, with a particular emphasis on interdisciplinary methods and practical experience.